IPTEKS STRATEGI PEMASARAN BBM NON SUBSIDI PADA PT PERTAMINA (PERSERO) BRANCH MARKETING SULUTENGGO REGION VII - Paraswati, Sawindri Dyah; Lintong, Diana Nova (Universitas Sam Ratulangi, 2018)
Because of the importance of fuel oil for community needs both for household, business, transportation and industrial sectors. As the largest oil and gas company in Indonesia, even globally, Pertamina certainly has a specific strategy to market its products. Competition in the retail business of non-subsidized fuels is strongly influenced by government policies in terms of determining the price of shared fuels. The marketing of PT Pertamina Sulutenggo Cabang VII Daerah has the duty to market fuel oil to all areas of Sulutenggo and also the company carries out various strategies to survive on the market. In October 2018 Pertamina had just raised non-subsidized fuel prices throughout Indonesia, the prices set were not so much different from other regions, except for areas affected by natural disasters such as NTB and Central Sulawesi for the time being they did not rise. For now PT Pertamina Marketing Sulutenggo Branch focuses on the marketing strategy of non-subsidized fuels by holding various events, recently PT Sulutenggo Branch Marketing in commemoration of the national customer day on September 4, 2018, Pertamina held an event at the gas station. Coco Samrat by distributing gifts to customers who buy non-subsidized fuel, such an event is also part of the prtamina strategy in marketing non-subsidized products. With this analysis carried out with the title of marketing strategy so that it aims to determine the implementation of marketing strategies for Non-Subsidized BBM PT Pertamina Marketing Sulutenggo Branch. The analysis used in this strategy is the marketing mix, which is